Gastric Duplication Cyst in 4 Years Male Child: A Rare Case Report - Ingle, Yamini; Patil, Saurabh Shyamsunder; Londhe, Mangesh (Journal of Nepal Paediatric Society, 2022)
Gastric duplication cyst is an unusual congenital malformation of the gastrointestinal tract representing 4% of all alimentary tract duplications. Clinically the patients may remain asymptomatic or symptoms can be nonspecific, which include abdominal mass, pain, nausea and emesis. We report a four year old male child who presented with intermittent pain in abdomen. The child was evaluated for the same by radiology which suggested a duplication cyst in epigastric region. The child underwent excision for the same following which histopathology confirmed the diagnosis of gastric duplication cyst (Gastric mucosal cyst).